2004
DOI: 10.1515/ling.2004.034
|View full text |Cite
|
Sign up to set email alerts
|

Some knowledge children dont lack

Abstract: Experimental studies on children's understanding of indefinite NPs and negation report a systematic non-adult interpretation of sentences like ''The detective didn't find some guys'' (see Musolino 1998). In this article, we question whether these findings require a grammatical explanation. We draw upon the observation that negative statements are generally used to point out discrepancies between the facts and the listener's expectations, and that this felicity condition was not satisfied in previous studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 10 publications
6
59
0
Order By: Relevance
“…The fact that Hungarian adult language is more isomorphic than Hungarian child language is also incompatible with the "grammatical" approach of Musolino (1998), claiming that the initial assumption that children set out with is isomorphic scope marking, which they only give up if they meet with evidence to the contrary. Gualmini's (2004;2008) alternative theory, according to which children's scope preferences are determined by pragmatic conditions, has proved to be irrelevant for the experiments surveyed, which tested minimal pairs not differing in any pragmatically meaningful way.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fact that Hungarian adult language is more isomorphic than Hungarian child language is also incompatible with the "grammatical" approach of Musolino (1998), claiming that the initial assumption that children set out with is isomorphic scope marking, which they only give up if they meet with evidence to the contrary. Gualmini's (2004;2008) alternative theory, according to which children's scope preferences are determined by pragmatic conditions, has proved to be irrelevant for the experiments surveyed, which tested minimal pairs not differing in any pragmatically meaningful way.…”
Section: Resultsmentioning
confidence: 99%
“…However, Musolino & Lidz (2003), Gualmini (2004), and Musolino & Lidz (2006) found that children can access the non-isomorphic reading of sentences like (1) if it is supported by the context, e.g., if (1) is uttered in a situation in which first all the horses jumped over a log, but only two of them managed to jump over the fence.…”
Section: Isomorphism As Consequence Of Parsing Difficultiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies showed children's sensitivity to contextual factors when interpreting ambiguous sentences; they demonstrated adultlike performance by children in accessing many of the interpretations that had eluded them in previous research. According to the authors of many of these later studies (e.g., Gualmini 2004b, Gualmini 2004aKrämer 2000;Musolino and Lidz 2006;Gualmini et al 2008), the cause of children's non-adult behaviour in the earlier work resided in their greater sensitivity to certain discourse-pragmatic factors, as compared to adults. Gualmini et al (2008), in particular, focused on one contextual factor, namely the question that was under consideration in the experimental context presented.…”
Section: The Question-answer Requirementmentioning
confidence: 99%